RNA-sequencing analysis of the Diquat-degrading yeast strain Meyerozyma guilliermondii Wyslmt and the discovery of Diquat degrading genes - Wang, Fangyuan; Kong, Lingwei; Guo, Jing; Song, Xiuli; Tao, Bo; Han, Yujun (Frontiers in Microbiology, 2022)
Diquat is used in agricultural contexts to control the growth of broadleaf and grassy weeds in both terrestrial and aquatic areas. Diquat can be readily absorbed by the soil and can remain therein for extended periods of time, altering the local microenvironment. In this study, the Meyerozyma guilliermondii Wyslmt yeast strain, which is capable of degrading Diquat, was isolated from soil exposed to long-term Diquat treatment. Over a 7-day incubation period, this strain was able to remove 42.51% of available Diquat (100 mg/L). RNA-Seq was performed to assess changes in gene expression in this yeast strain over the course of Diquat degradation, revealing 63 and 151 upregulated and downregulated genes, respectively. KEGG pathway enrichment analysis revealed these genes to be most highly enriched in the carbohydrate metabolism pathway. Through functional annotation and gene expression analyses, we identified seven genes were predicted to be involved in Diquat biodegradation. Results of qRT-PCR assays indicated that the relative mRNA expression levels of these seven genes were significantly higher relative to the control group. Together these analyses led to the identification of Pdr676 as a candidate Diquat-degrading gene. When a pET-Pdr676 vector was expressed in E. coli BL21, this strain was able to remove 12.49% of provided Diquat (100 mg/L) over the course of a 7-day incubation. These results thus confirmed that the Pdr676 gene can promote Diquat degradation, with these studies having yielded an engineered BL21-pET-Pdr676 bacterial strain capable of degrading Diquat.